Acquittal Due to the Elimination of the Authority to Prosecute Criminal Charges for Class I Narcotics Crimes (Case Study of Decision Number: 90/Pid.Sus/2023/PN.Sdr) - Nurhasan, Muhammad Algifari; Arifullah, Achmad (UNISSULA Semarang, 2025)
The study aims to provide the legal implications of acquittal decisions due to the elimination of the authority to prosecute criminal acts of Class I Narcotics at the Sidenreng Rappang District Court as legal responsibility, and the judge's legal considerations in acquittal decisions due to the elimination of the authority to prosecute criminal acts of Class I Narcotics at the Sidenreng Rappang District Court. The sociological legal approach method is an approach to studying and discovering legal realities experienced in the field or an approach that is based on problems concerning legal matters and existing realities, using the theory of Pancasila Justice and the Legal System. The results of the research and discussion are that (1) The legal implications of the acquittal decision due to the elimination of the authority to prosecute criminal acts in Class I Narcotics crimes at the Sidenreng Rappang District Court as the defendant's legal responsibility is released from all criminal charges for the case, but the act charged is still recognized as having been committed. Other legal implications can result in two sides, namely it can have a good impact and can also have a bad impact on all parties. The positive impact of the acquittal decision is to provide justice, certainty and benefits to the defendant as one of the fulfillments of the objectives of the law. (2) The judge's legal considerations in the acquittal decision due to the elimination of the authority to prosecute criminal acts in Class I Narcotics crimes at the Sidenreng Rappang District Court, the judge considers several important things when issuing an acquittal decision due to the elimination of the authority to prosecute criminal acts. These things include evidence in court, charges, demands, witness statements, and other facts that support the judge's decision. In addition, the judge also considers legal and non-legal reasons, such as the defendant's background. The Supreme Court's decision stated that the defendant was not proven legally and convincingly guilty of committing the acts as charged in the public prosecutor's indictment.